SLANG LANGUAGE IN SOLIDIFYING IDENTITY AND SOLIDARITY: A SOCIOLINGUISTIC ANALYSIS OF THE EPISODE 'DUELING HATS' FROM THE COMEDY SKETCH 'KEY & PEELE' - Abdussalam Jabaruddin Yamjirin; Henry Yustanto; Wiwik Yulianti (Adisam Publisher, 2025)
This study examines the use of African-American slang in the episode